Normal and abnormal liquor volume and its correlation with perinatal outcome - Sharmila Ravi; Allirathinam; Senthil Priya; Prema Priya; Shankar Radhakrishnan (Barpeta Obstetrics and Gynaecological Society, 2019)
Aim: To assess and compare the perinatal outcome among mothers with normal and abnormal amniotic fluid volume. Methodology: A prospective comparative study was conducted for a period of one year from January 2016 to December 2016. Group I consist of 50 patients with normal amniotic fluid and group II consists of 50 patients with either oligohydramnios or polyhydramnios. Amniotic fluid index (AFI) was calculated using Phalen's four quadrant technique using ultrasound. The perinatal outcome was judged by assessing the fetal distress predicted by abnormal fetal heart rate (FHR) or meconium stained liquor, one minute and 5 minute Apgar score, frequency of admission to neonatal intensive care unit (NICU), baby weight of less than 10th percentile for gestation age and perinatal mortality. Results: Induction of labour, caesarean section and meconium stained liquor was found to be most common among the patients in group II (abnormal AFI) in comparison with normal AFI subjects and similarly the perinatal outcome measures like low birth weight, increased frequency of admission to NICU due to respiratory distress and a low APGAR score was more commonly found in abnormal AFI group and the difference was found to be statistically significant. Conclusion: AFI measurement in antepartum or intrapartum period can help to identify women who need increased antepartum surveillance for pregnancy complications and such women should be managed in a special unit to combat the complications effectively.